2019
DOI: 10.1108/ssrp-09-2018-0036
|View full text |Cite
|
Sign up to set email alerts
|

“Escape the Room” – a strategy for problem-based learning and student inquiry

Abstract: Purpose Problem-based learning (PBL) has long been a regular feature in professions outside K-12 education and is growing in social studies education in recent years. PBL is built around student inquiry into an “ill-structured” or “messy” problem (Wieseman and Cadwell, 2005, p. 11). These inquiries are open ended, largely autonomous and student driven (Savin-Baden, 2014). The collaborative nature of PBL scenarios allows students to work with real-world concepts and skills to solve problems (Ferreira and Trudel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In order to be able to do this, a minimum of two teachers must participate in the EHE and one of them must become the game master. Other studies in the literature underline the role of the game master during the performance of EER [40,52], since this figure offers extra guidance.…”
Section: Discussionmentioning
confidence: 99%
“…In order to be able to do this, a minimum of two teachers must participate in the EHE and one of them must become the game master. Other studies in the literature underline the role of the game master during the performance of EER [40,52], since this figure offers extra guidance.…”
Section: Discussionmentioning
confidence: 99%
“…By adopting a problem-based teaching method, teachers managed to expose learners to illstructured and business-related problems. Pearcy et al (2019) concur that teachers should expose learners to messy, ill-structured and untidy problems in their pedagogical practices. In addition to this, the study found that teachers adopt the discussion method in their classrooms.…”
Section: Discussionmentioning
confidence: 95%
“…Their analytical skills and ability to gather relevant information, assist them in finding proper solutions to problems. Pearcy et al (2019) suggest that teachers should expose learners to ill-structured, messy and untidy situations to develop problem-solving skills. Mustofa and Hidayah (2020) maintain that teachers should not limit learners by teaching them factual knowledge only but should also expose them to ill-structured problems to nurture their problem-solving skills.…”
Section: Problem-solving Skillsmentioning
confidence: 99%
“…EERs can also be used for problem-based learning (PBL) since their features are also included in the ER scenario with an "ill-structured" or "messy" problem within a "real-life scenario" and respective concepts. Students are encouraged to solve challenges they can find through open-ended tasks, endorsing their autonomy and collaboration with their peers (Pearcy et al, 2019, Krekhov et al, 2021.…”
Section: Educational Escape Roommentioning
confidence: 99%